Infective cause of childhood leukaemia and wartime population mixing in Orkney and Shetland, UK. - Kinlen, L; Balkwill, A (2001)
In Orkney and Shetland (the UK's northernmost islands), during World War II, local people were outnumbered by servicemen stationed there in case of a northern invasion. Such rural-urban population mixing promotes contact between susceptible and infected individuals. We compared childhood leukaemia mortality in wartime and postwar cohorts of Orkney and Shetland children. Childhood leukaemia increased 3.6-fold, (p=0.001) in the wartime, but not in the postwar, cohort compared with national Scottish rates. These findings add to the evidence for infection as a cause of childhood leukaemia.